2022
DOI: 10.1101/2022.07.21.22277900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phenome-wide Mendelian randomization study of plasma triglycerides and 2,600 disease traits

Abstract: BackgroundCausality between plasma triglyceride (TG) levels and atherosclerotic cardiovascular disease (ASCVD) risk remains controversial despite more than four decades of study and two recent landmark trials, STRENGTH and REDUCE-IT. Further unclear is the association between TG levels and non-atherosclerotic diseases across organ systems.MethodsHere, we conducted a phenome-wide, two-sample Mendelian randomization (MR) analysis using inverse-variance weighted (IVW) regression to systematically infer the causal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Genome-wide association studies have revealed that susceptibility to ischaemic heart disease is associated with the presence of genes involved in TG metabolism [19]. Similarly, Mendelian randomisation studies indicate a causal relationship between TG metabolism and the risk of atherosclerosis and its complications, including ischaemic heart disease, increased in hypertriglyceridaemia by 33% [20].…”
Section: Atherosclerotic Plaque Progressionmentioning
confidence: 99%
“…Genome-wide association studies have revealed that susceptibility to ischaemic heart disease is associated with the presence of genes involved in TG metabolism [19]. Similarly, Mendelian randomisation studies indicate a causal relationship between TG metabolism and the risk of atherosclerosis and its complications, including ischaemic heart disease, increased in hypertriglyceridaemia by 33% [20].…”
Section: Atherosclerotic Plaque Progressionmentioning
confidence: 99%